Quantum Computing Explained - McMahon, David (Wiley, 2007)
A self-contained treatment of the fundamentals of quantum computing This clear, practical book takes quantum computing out of therealm of theoretical physics and teaches the fundamentals of thefield to students and professionals who have not had training inquantum computing or quantum information theory, including computerscientists, programmers, electrical engineers, mathematicians,physics students, and chemists. The author cuts through theconventions of typical jargon-laden physics books and insteadpresents the material through his unique "how-to" approach andfriendly, conversational style.Readers will learn how to carry out calculations with explicitdetails and will gain a fundamental grasp of:Quantum mechanicsQuantum computationTeleportationQuantum cryptographyEntanglementQuantum algorithmsError correctionA number of worked examples are included so readers can see howquantum computing is done with their own eyes, while answers tosimilar end-of-chapter problems are provided for readers to checktheir own work as they learn to master the information.Ideal for professionals and graduate-level students alike,Quantum Computing Explained delivers the fundamentals ofquantum computing readers need to be able to understand currentresearch papers and go on to study more advanced quantum texts.